2012
DOI: 10.3892/ijmm.2012.1154
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cardiac hypertrophy by probiotic-fermented purple sweet potato yogurt in spontaneously hypertensive rat hearts

Abstract: Cardiovascular hypertrophy is a common feature of hypertension and an important risk factor for heart damage. The regression of cardiovascular hypertrophy is currently considered an important therapeutic target in reducing the omplications of hypertension. The aim of this study was to investigate the inhibition of cardiac hypertrophy by probiotic-fermented purple sweet potato yogurt (PSPY) with high γ-aminobutyric acid (GABA) content in spontaneously hypertensive rat (SHR) hearts. Six-week-old male SHRs were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Hypertension induces pathological cardiac hypertrophy secondary to the pressure overload, thereby contributing to decreased cardiac function and increased cardiac apoptosis (21,22). In a previous study, we demonstrated that PSPY exerted anti-hypertrophic effects in the hearts of SHRs by interfering with the IGF-II signaling pathway and the IL-6-related-ERK5 pathway (23). In the present study, the results of cardiomyocyte loss, as shown by TUNEL assay are consistent with those of previous studies describing the gradual cardiac decompensation in SHR hearts (24).…”
Section: Discussionmentioning
confidence: 94%
“…Hypertension induces pathological cardiac hypertrophy secondary to the pressure overload, thereby contributing to decreased cardiac function and increased cardiac apoptosis (21,22). In a previous study, we demonstrated that PSPY exerted anti-hypertrophic effects in the hearts of SHRs by interfering with the IGF-II signaling pathway and the IL-6-related-ERK5 pathway (23). In the present study, the results of cardiomyocyte loss, as shown by TUNEL assay are consistent with those of previous studies describing the gradual cardiac decompensation in SHR hearts (24).…”
Section: Discussionmentioning
confidence: 94%
“…Our data show that kefir treatment of SHR was able to attenuate the impaired baroreflex sensitivity by restoring part of the cardiac autonomic activity. A possible mechanism for the beneficial effect of kefir on the vagal-mediated baroreflex sensitivity in this model of hypertension could be through the reduction of the cardiac hypertrophy as observed by using different probiotics (Lin et al, 2012 ; Gan et al, 2014 ; Gómez-Guzmán et al, 2015 ). Therefore, in addition to other non-pharmacological therapies, such as physical exercise (Ceroni et al, 2009 ), the chronic administration of the nutritional probiotic kefir appears to have beneficial actions targeting the restoration of the balance between the vagal and sympathetic activities and improving the baroreflex function in hypertensive subjects.…”
Section: Discussionmentioning
confidence: 94%
“…These foods often contain more nutrients, such as nuts rich in both 3-n PUFA and polyphenols, and are easier to administer and could also be enriched with additional nutraceutics, such as yogurt with antioxidants. Table 5 shows some functional foods, presented in this review, that are capable of modifying the expression of adipokines, myokines, and cardiokines [52,53,79,81,83,156,157,177]. Therefore, the action of functional foods will have to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In rats an myocardial infarction was induced and after 6 weeks of supplementation the authors have detected an reduction of myocardial hypertrophy associated with decreased ANP levels [176] (Table 2). In the same manner, probiotic-fermented purple sweet potato yogurt supplementation improves cardiac hypertrophy downregulating ANP and BNP expression in hypertensive rat hearts [177] (Table 5).…”
Section: Natriuretic Peptides: Nutritional Interventionsmentioning
confidence: 93%